Pengaruh Flexible Working Arrangements dan Perceived Supervisor Support terhadap Work Engagement dan Employee Performance: Studi Empiris pada Organisasi Keuangan Pemerintah di Indonesia - Rahmawati, Dwi; Savitri Pusparini, Elok (Jurnal Manajemen dan Organisasi, 2023)
Organizations generally look for ways to achieve high performance from employees but sometimes ignore the important role of work engagement, as in the case of public sector organizations, especially after the COVID-19 pandemic. The main objective of this research is to determine the effect of flexible working arrangements and perceived supervisor support on work engagement and employee performance. We surveyed 321 civil servants who carry out flexible working arrangements at Government Financial Organization. We identify the effect of flexible working arrangements and perceived supervisor support on work engagement and the role of work engagement as a mediator of flexible working arrangements and perceived supervisor support on employee performance using a covariance-based structural equation modeling (CB-SEM) approach. The findings show that flexible working arrangements and perceived supervisor support have a positive and significant effect on work engagement and employee performance through the mediation of work engagement. Furthermore, work engagement has a positive and significant impact on employee performance. This study contributes to an investigation into the predictors that influence employee performance considering the limited research on work engagement and employee performance in the Indonesian public sector, especially after changes in work patterns after the COVID-19 pandemic.